2013
DOI: 10.1016/j.molcel.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response Diversity of NFAT Isoforms in Individual Living Cells

Abstract: Processing of external information by mammalian cells often involves seemingly redundant isoforms of signaling molecules and transcription factors. Understanding the functional relevance of coexpressed isoforms that respond to the same signal and control a shared set of genes is still limited. Here we show, using imaging of individual living mammalian cells, that the closely related transcription factors NFAT1 and NFAT4 possess distinct nuclear localization dynamics in response to cell stimulation. NFAT4 shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 36 publications
(41 reference statements)
1
109
0
Order By: Relevance
“…Recent work shows that pulsatile regulation occurs in diverse mammalian systems including NF-AT, [17] p53 [18], Erk signaling ([19], TGF-β signaling [20] and NF-κB [21-23]. Moreover, many bacterial systems such as persistence in Mycobacterium smegmatis [24] and bacterial competence [25], sporulation [26] and stress response in Bacillus subtilis [27], employ pulsing.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work shows that pulsatile regulation occurs in diverse mammalian systems including NF-AT, [17] p53 [18], Erk signaling ([19], TGF-β signaling [20] and NF-κB [21-23]. Moreover, many bacterial systems such as persistence in Mycobacterium smegmatis [24] and bacterial competence [25], sporulation [26] and stress response in Bacillus subtilis [27], employ pulsing.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, frequency encoding is likely to be more robust and to convey more information than amplitude encoding for intracellular signaling, since information can be encoded both in the amplitude of the oscillations and in their frequency, as well as the potential for encoding multiple frequencies in a complex oscillating signal [111]. Both theoretical [112] and experimental analyses in non-neuronal cells [113][114][115][116] have shown that an oscillating signal can lead to a more consistent output than a non-oscillating signal, and frequency encoded signaling was recently proposed to function in axon growth and length control in neurons [117,118]. Regardless of whether the macromolecular signals in synapse to nucleus communication are amplitude or frequency encoded, it will be intriguing to determine which aspects of plasticity require long-distance protein messengers.…”
Section: Reviewmentioning
confidence: 99%
“…Recently, fluorescent reporter molecules have been developed to track signaling pathways in real time (Nelson et al, 2004;Purvis et al, 2012;Regot et al, 2014;Yissachar et al, 2013). Results generated by using these approaches, have shown not only that signaling dynamics of individual cells tend to be hidden within population averages but also that some pathways yield sustained responses, others produce transient effects and still others show variable patterns depending upon either the strength or duration of the signaling input (Albeck et al, 2013;Batchelor et al, 2011;Nelson et al, 2004;Purvis et al, 2012;Yissachar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Results generated by using these approaches, have shown not only that signaling dynamics of individual cells tend to be hidden within population averages but also that some pathways yield sustained responses, others produce transient effects and still others show variable patterns depending upon either the strength or duration of the signaling input (Albeck et al, 2013;Batchelor et al, 2011;Nelson et al, 2004;Purvis et al, 2012;Yissachar et al, 2013). Some signaling pathways also have been found to exhibit all-or-none (=digital) outcomes (Tay et al, 2010), whereas others demonstrate graded (=analog) responses (Toettcher et al, 2013).…”
Section: Introductionmentioning
confidence: 99%